Türkçe ve Arapçada Sessiz Harfler Karşılaştırma Çalışması (Journal of the College of Languages (JCL), 2010)
This is an abstract of a thesis entitled A contrastive study of Turkish and Arabic consonants . In fact , languages have different numbers of sounds . Speakers of a language find it difficult to learn foreign language sounds whose native language do not have . The thesis is contrastive study that shows similarit ies and differences between Turkish and Arabic consonants . The study sheds light on the difficulties arab students of Turkish face because of such consonant differen ces . It shows the negative role Arabic words borrowed by Turkish plays in the way the students pronounce Turkish .